Actinomycin D induces non-random apoptotic DNA breakpoints in human leukemia HL-60 cells. - Lin, Lifang. (2011)
Apoptosis is a programmed cell death that is induced by prolonged cellular stress. During apoptosis, caspase-activated DNase cleaves DNA at the internucleosomal regions to produce an “apoptotic ladder” that consists of multiples of 180-200bp. We postulate that these apoptotic DNA breakpoints are non-random and may be associated with cancer. Previously, our laboratory sequenced the 180-200bp band of the apoptotic ladder DNA of human leukemia HL-60 cells after treating them with actinomycin D for 19 hours. This study aims to validate these results using quantitative PCR at 13 sites near genes and to examine the differences between apopotic breakpoints of HL-60 cells after 4 hours and 19 hours of actinomycin D treatment. Our results showed that actinomycin D-induced apoptosis in HL-60 cells produced specific apoptotic DNA breakpoints, which was consistent with the previous sequencing studies. Some sites of cleavage were near to apoptosis-associated genes (e.g.BIM) and translocated-associated genes (e.g.CREB3L2). In addition, there was no significant difference in the apoptotic breakpoints between 4 hours and 19 hours of actinomycin D-treated HL-60 cells. The discovery of these sites near genes allows us to understand apoptosis in cancer cells better and may provide a platform for further research in cancer treatment.